Usage of Open Access institutional repositories in some of the European peripheral scientific communities - Hebrang Grgić, Ivana (2011)
In the introduction, institutional repositories and Open Access movement are explained. In literature review, citation impact of Open Access articles are discussed. Further on, differences between scientifically mainstream and peripheral countries are emphasized. Two important factors in defining peripheral scientific communities - language and economy - are explained. Scientists in peripheral scientific communities sometimes communicate in "small" language, and sometimes their countries' economy is marked as "developing" or "semi-developed". Problems of seven European semi-developed and developed countries with official languages other than English are discussed (Italy, Poland, Greece, Hungary, Bulgaria, Croatia, Slovenia). Institution repositories, especially if they are Open Access repositories, can significantly increase research impact of their institutions. Number and productivity of Open Access institutional repositories in the seven countries will be discussed.
ENG